The Pancreatic Head is Larger than often Assumed - Pirri, C.; Cui, X. W.; De Molo, C.; Ignee, A.; Schreiber-Dietrich, D. G.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2013)
Reference values for B-mode abdominal ultrasound are controversially discussed in the literature mainly due to the lack of data and non-standardized examination techniques. A cohort of 100 patients was prospectively examined. Patients with hepatobiliary diseases including gallstones, acute or chronic pancreatitis (n = 13) and non-adequate visualization (n = 10) were excluded from statistical analysis. Therefore, 77 patients were analyzed including 52 female and 25 male healthy subjects regarding the biliopancreatic system (median age ± SD: 56 ± 18 years [minimum: 22 and maximum 93 years]). The mean value of the cranio-caudal diameter of the pancreatic head was 49 ± 10 [26 – 77] mm(mean ± SD [minimum − maximum]) which is larger than usually reported except in one study. The size of the pancreatic head is often larger than assumed which is of importance to know to exclude pancreatic pathology below the level of the common bile duct.
Keywords: reference values; size; adenocarcinoma; pancreatitis; tumors